Integration of Renewable Energy Technologies in Smart Building Design for Enhanced Energy Efficiency and Self-Sufficiency - Ochuko Felix Orikpete; Samuel Ikemba; Daniel Raphael Ejike Ewim (The Journal of Engineering and Exact Sciences)
This paper investigates the integration of renewable energy technologies (RETs) in the design of smart buildings with the aim of achieving enhanced energy efficiency and self-sufficiency. As the demand for sustainable building practices grows, it becomes imperative to harness renewable energy sources and leverage advanced control mechanisms. This paper provides a comprehensive overview of the current state-of-the-art RETs, including photovoltaics, wind turbines, solar thermal systems, and energy storage solutions. The focus of the paper extends to the convergence of these technologies with smart building systems, such as energy management systems, building automation, and advanced sensors and controls. Through in-depth case studies, the paper demonstrates how the synergetic integration of RETs in smart buildings can lead to significant reductions in energy consumption, lower carbon footprints, and an enhanced ability for buildings to be energy self-reliant. Furthermore, the paper delves into potential challenges and barriers faced in the adoption of these technologies and offers strategies and recommendations to overcome them. Our findings underscore the transformative potential of merging RETs with smart building designs and emphasize the need for further research and policy support in this domain.